PELAKSANAAN TEKNIK SUPERVISI INDIVIDUAL SEBAGAI IMPLEMENTASI KERJA GURU DI SDN 12 LUNANG - Halijah, Halijah (Jurnal Manajemen Pendidikan, 2018)
Based on the observations that the researchers did to the teachers at SDN 12 Lunang, it was found that the ability of teachers in the implementation of teacher work was still low. The purpose of this study was to improve the ability of teachers in the implementation of teacher work through individual supervision techniques at SDN 12 Lunang. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 9 Lunang 12 Elementary School Teachers. Research data was collected using observation sheets. Data is analyzed using percentages. The results showed that through individual supplementary techniques can improve the ability of teachers in the implementation of teacher work. This is evidenced by an increase in the ability of teachers in the implementation of teacher work in cycle I to cycle II. The average ability of teacher skills in Teacher Ability in the implementation of teacher work in the first cycle was 45.33 in the Less category and in the second cycle was 84 in the good category.